The tribe Dysoniini part IV: New species of Quiva Hebard, 1927 (Orthoptera: Tettigoniidae: Phaneropterinae) from Brazilian rainforest and some clarifications - Cadena-Castañeda, Oscar J.; Mendes, Diego Matheus De Mello; Sovano, Rafael S. Da Silva (Zootaxa, 2015)
Two new species of the genus Quiva: Quiva buhrnheimi n. sp. and Quiva gutjahrae n. sp. from Brazilian Amazon are described. Determinations for distributional data previously published by Sovano & Mendes (2013) are clarified and the synonymy of Ituana dorisae under Q. abacata is confirmed. In this paper, an updated key to subgenus Quiva is provided.